2022
DOI: 10.1002/biof.1890
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized phospholipids and lipoprotein‐associated phospholipase A2 (Lp‐PLA2) in atherosclerotic cardiovascular disease: An update

Abstract: Inflammation and oxidative stress conditions lead to a variety of oxidative modifications of lipoprotein phospholipids implicated in the occurrence and development of atherosclerotic lesions. Lipoprotein-associated phospholipase A2 (Lp-PLA 2 ) is established as an independent risk biomarker of atherosclerosis-related cardiovascular disease (ASCVD) and mediates vascular inflammation through the regulation of lipid metabolism in the blood and in atherosclerotic lesions. Lp-PLA 2 is associated with low-and high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 133 publications
(334 reference statements)
0
10
1
Order By: Relevance
“…Oxidized phospholipids have previously been shown to increase in insulin resistant individuals and be associated with the pathogenesis of oxidative stress-related diseases, including CVD (Fruhwirth et al, 2007;Sun et al, 2016;Que et al, 2018). Yet, in previous work, increased circulating oxidized phospholipids correlated with Lp-PLA2 levels (Pantazi et al, 2022). In our study, we found oxidized phospholipids were specifically elevated in the T2D-DL group, even though there was no statistically significant difference between the number of subjects in the T2D-DL and T2D-M groups who had clinically elevated Lp-PLA2 levels.…”
Section: Metabolites Associated With Cvd Risk Are Reduced With Metfor...contrasting
confidence: 69%
“…Oxidized phospholipids have previously been shown to increase in insulin resistant individuals and be associated with the pathogenesis of oxidative stress-related diseases, including CVD (Fruhwirth et al, 2007;Sun et al, 2016;Que et al, 2018). Yet, in previous work, increased circulating oxidized phospholipids correlated with Lp-PLA2 levels (Pantazi et al, 2022). In our study, we found oxidized phospholipids were specifically elevated in the T2D-DL group, even though there was no statistically significant difference between the number of subjects in the T2D-DL and T2D-M groups who had clinically elevated Lp-PLA2 levels.…”
Section: Metabolites Associated With Cvd Risk Are Reduced With Metfor...contrasting
confidence: 69%
“…A recent study suggested a mechanism for this relation depends on the generation of ROS causing oxidized phospholipids subspecies that were degraded enzymatically by activation of lipoprotein-associated phospholipase A2 forming lysophospholipids which in turn stimulate the production of the inflammatory cytokines; TNF-α and IL-6, promote the expression of adhesion molecules and attract macrophages to the arterial intima causing atherosclerotic changes [37] .…”
Section: Discussionmentioning
confidence: 99%
“…From the metabolic pathways of EICs, ECBs and SPMs shown in Figure 1 , Figure 2 and Figure 3 , it is apparent that these families of bioactive lipids share key enzymes, such as the lipase responsible for the release from phospholipid precursors (PLA 2 ) and three oxygenases able to generate from AA: (i) epoxyeicosatrienoic acids (CYP450); (ii) 12-hydroxyeicosatetraenoic acids (12-LOX); and (iii) cyclic prostanoid(-like) oxidative derivatives (COX-2). Of note, PLA 2 belongs to a superfamily of enzymes that play major roles in several pathophysiological processes, e.g., mast cell biology [ 45 ], atherosclerotic cardiovascular disease [ 46 ], and gastrointestinal diseases [ 47 ]. Unsurprisingly, PLA 2 enzymes are able to mobilize unique bioactive lipids in multiple ways that are spatiotemporally regulated, thus triggering distinct signaling pathways.…”
Section: Interactions In Lipid Signaling Pathwaysmentioning
confidence: 99%